Brief group counseling focuses on the solution to improve the independence of decision making students in class XI at SMKN 2 Kediri - Risky Frahmatika Dewi; Khususiyah Khususiyah; Galang Surya Gumilang (TERAPUTIK: Jurnal Bimbingan dan Konseling, 2017)
This study aimed to obtain accurate data and know the effectiveness of counseling groups that focus on solutions to improve students' independence in decision making. This study uses quasi-experimental research with the quantitative approach. The process of data analysis using descriptive analysis and hypothesis analysis using paired sample t test. Research subjects for this study amounted to 10 respondents who are divided to two groups. Each group consists of 5 students of class XI SMKN 2 Kediri. Results of final data analysis are done by using parametric statistic test that is Independent Sampling Test with significance level 0,05 obtained by Sig. (2-tailed) are 0,000 <0,05 then Ho is rejected. The results from this study indicate that focus group counseling services focused on this solution is effective to improve the independence of decision making students' class XI SMKN 2 Kediri.